CONSTRUCTION OF INTERGRATIVE PLASMIDS FOR RECOMBINATION OF SHEEPPOX VIRUS GENOME - Chervyakova , O.V.; Strochkov , V.M.; Tailakova , E.T.; Sultankulova , K.T.; Samdybayev , N.T. (Eurasian Journal of Applied Biotechnology, 2017)
The ability of capripoxviruses to elicit cellular and humoral immune responses, incorporate extended DNA sequences into host genomes, and display a safety profile are important considerations in the development of vector vaccines for animals and humans. The aim of our study was to design and construct recombinant plasmid DNAs for the recombination of capripoxvirus genomes. Two genetic constructs were developed, pINT-TKsppv and pINT-RRsppv, which contained sequences of sheeppox virus genome DNA insufficientfor virus replication (thymidine kinase gene and small ribonucleotidereductase gene) as well as a cassette for target gene expression and selective marker (gpt). Control of the expression of target genes will be driven by a synthetic early/late vaccinia virus promoter. These constructs will be used in the generation of recombinant sheeppox viruses expressing target antigens.